Picenum and the Ager Gallicus at the dawn of the Roman conquest : landscape archaeology and material culture - Boschi, Federica; Giorgi, Enrico; Vermeulen, Frank (Access archaeology., 2020)
This volume presents a coherent collection of papers presented at an International Workshop (held in Ravenna, 13-14 May 2019) which focused on the transition between Italic culture and Romanised society in the central Adriatic area - the regions ager Gallicus and Picenum under Roman dominance - from the fourth to the second centuries BCE.